Dynamic Transformations of the Content Characteristics of Creativity in Students with Different Cognitive Styles - I. S. Morozova (Kemerovo State University, 2021)
The research featured the effect of the dominant cognitive style on the creativity of college students. The research objective was to study the dynamic transformations of the content characteristics of creativity in college students with different cognitive styles. The article introduces various approaches to the concepts of cognitive style and creativity in foreign and domestic psychology. A set of experiments revealed the necessity to take into account the dominant cognitive style as a creativity determiner and proved the effect of cognitive style on creativity. The authors studied the dynamics of creativity in students, based on their field dependence / independence and integrity / differentiality. The field-dependent students appeared to be more involved in the academic information al environment. They were unable to change their attitudes and opinions, even in conditions of directional influence during the psychological training. The field-independent student showed better creativity after the psychological training as they strived to develop their own attitude to all incoming information. The participants with predominating differentiality were more creative, while their differential state vector depended on their ability to satisfy their need to detail the information they perceived and produced.